On communitarian and constitutional approaches to international law - Rauber, Jochen (Leiden journal of international law, 2013)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0922156512000726/resource/name/firstPage-S0922156512000726a.jpg